2012
DOI: 10.36076/ppj.2012/15/e143
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Fluoroscopically Directed Facet Joint Nerve Blocks: A Prospective Evaluation of 7,500 Episodes with 43,000 Nerve Blocks

Abstract: Background: Chronic spinal pain is common along with numerous modalities of diagnostic and therapeutic interventions utilized, creating a health care crisis. Facet joint injections and epidural injections are the 2 most commonly utilized interventions in managing chronic spinal pain. While the literature addressing the effectiveness of facet joint nerve blocks is variable and emerging, there is paucity of literature on adverse effects of facet joint nerve blocks. Study Design: A prospective, non-randomized stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 79 publications
0
38
1
3
Order By: Relevance
“…16 A study that reported on complications from 3162 MBBs found superficial bleeding or hematomas in 0.1%-0.4% of the patients. 273 Lumbar MBB and RFA are currently classified as 'low-risk' procedures in the guidelines on spinal procedures in patients on anticoagulant and antiplatelet medications formulated collaboratively by the American Society of Regional Anesthesia and Pain Medicine (ASRA) and other societies. 276 This risk classification was based on a study by Endres et al 277 that reported a 0% complication rate in 1836 patients who continued their anticoagulant therapy.…”
Section: Vascular Penetration and Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…16 A study that reported on complications from 3162 MBBs found superficial bleeding or hematomas in 0.1%-0.4% of the patients. 273 Lumbar MBB and RFA are currently classified as 'low-risk' procedures in the guidelines on spinal procedures in patients on anticoagulant and antiplatelet medications formulated collaboratively by the American Society of Regional Anesthesia and Pain Medicine (ASRA) and other societies. 276 This risk classification was based on a study by Endres et al 277 that reported a 0% complication rate in 1836 patients who continued their anticoagulant therapy.…”
Section: Vascular Penetration and Injurymentioning
confidence: 99%
“…These events were more severe and common when anticoagulants were discontinued, while there was no difference in the reported occurrence of bleeding complications stratified by whether or not anticoagulants were continued. 273 Based on the literature, the ASRA anticoagulation guidelines committee placed thoracic and lumbar MBB and RFA in the lowrisk procedure category, especially in patients who are at a high risk of thromboembolic events. This is consistent with guidelines from the SIS, 278 279 and represented a change from the previous version of the ASRA guidelines issued in 2015, in which thoracolumbar procedures were classified as 'intermediate risk'.…”
Section: Vascular Penetration and Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Large, observational studies of epidural and other spinal injections were consistent with randomized trials in reporting rare serious adverse events, though minor adverse events such as local hematoma, bleeding, return of blood, and dural puncture were more common. [157][158][159][160] For example, in a recent study that also evaluated the largest sample, there were no cases of nerve damage, infection, abscess, or epidural hematoma following 2,760 lumbar epidural injections under fluoroscopic guidance. 158 Rates of profuse bleeding ranged from 0.2 to 0.8 percent depending on the approach used.…”
Section: Observational Studies On Harmsmentioning
confidence: 99%
“…For patients who gain their consciousness, if they tried to sit or stand up again, there may be unconsciousness recurrence. Nausea, sweating and pallor from several minutes to several hours may be in place [7][8][9].…”
Section: Introductionmentioning
confidence: 99%